Antimicrobial Blue Light for Prevention and Treatment of Highly Invasive Vibrio vulnificus Burn Infection in Mice - dos Anjos, Carolina; Leanse, Leon G.; Liu, Xiaojing; Miranda, Hugo V.; Anderson, R. Rox; Dai, Tianhong (Frontiers in Microbiology, 2022)
Vibrio vulnificus is an invasive marine bacterium that causes a variety of serious infectious diseases. With the increasing multidrug-resistant variants, treatment of V. vulnificus infections is becoming more difficult. In this study, we explored antimicrobial blue light (aBL; 405 nm wavelength) for treatment of V. vulnificus infections. We first assessed the efficacy of aBL against 5 strains of V. vulnificus in vitro. Next, we identified and quantified intracellular porphyrins in V. vulnificus to provide mechanistic insights. Additionally, we measured intracellular reactive oxygen species (ROS) production and bacterial membrane permeabilization following aBL exposures. Lastly, we conducted a preclinical study to investigate the efficacy and safety of aBL for prevention and treatment of V. vulnificus burn infection in mice. We found that aBL effectively killed V. vulnificus in vitro in both planktonic and biofilm states, with up to a 5.17- and 4.57-log10 CFU reduction being achieved, respectively, following an aBL exposure of 216 J/cm2. Protoporphyrin IX and Coproporphyrins were predominant in all the strains. Additionally, intracellular ROS was significantly increased following aBL exposures (P<0.01), and there was evidence of aBL induced permeabilization of the bacterial membrane (P<0.0001). In the preclinical studies, we found that female mice treated with aBL 30 min after bacterial inoculation, showed a survival rate of 81% following 7 days observation, while only 28% survival was observed in untreated female mice (P<0.001). At 6 h post-inoculation, an 86% survival was achieved in aBL-treated female mice (P = 0.0002). For male mice, 86% and 63% survivals were achieved when starting aBL 30 min and 6 h after bacterial inoculation, respectively, compared to 32% survival in the untreated mice (P = 0.0004 and P = 0.04). aBL did not reduce cellular proliferation or induce apoptosis. We found 5 cytokines were significantly upregulated in the males after aBL treatment, including MCSF (P < 0.001), MCP-5 (P < 0.01), TNF RII (P < 0.01), CXCL1 (P < 0.01), and TIMP-1 (P < 0.05), and one in the females (TIMP-1; P < 0.05), suggesting that aBL may induce certain inflammatory processes. In conclusion, aBL may potentially applied to prevent and treat V. vulnificus infections.